A Study on Use of Electronic Resources and Information in National Law University of India: Investigating Access and Utilization of Electronic Resources in National Law University of India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study aims to know the use of Electronic Resources and Information in National Law University of India. The main focus of the study is to know the availability and use of Electronic Resources, services and facilities in national law university libraries. The present study is conducted to know frequency and purposes of using national law Universities, adequacy of print and electronic law electronic resources.